CARBAPENEMASE GENE SPECTRUM AND COLISTIN SUSCEPTIBILITY OF PSEUDOMONAS AERUGINOSA ISOLATES FROM INPATIENTS AT NGUYEN TRI PHUONG HOSPITAL (Vietnam Journal of Community Medicine, 2026)
of Pseudomonas aeruginosa isolates collected from inpatients at Nguyen Tri Phuong Hospital during 2024-2025.Methods: 88 non-duplicate isolates underwent antimicrobial susceptibility testing (CLSI 2025), Colistin MIC determination by E-test, and multiplex real‑time PCR screening for blaNDM, blaIMP, blaVIM, blaKPC and mcr-1-mcr-10 genes.Results: Resistance to Imipenem and Meropenem ranged from 42-46%, whereas all isolates remained susceptible to Colistin. Among 32 carbapenemase‑producing isolates, blaNDM predominated (over 50%), surpassing blaIMP (28-29%), with a strong correlation between blaNDM/blaIMP carriage and Carbapenem-resistant phenotypes (p < 0.00001). No mcr variants were detected.Conclusion: The predominance of blaNDM within the P.aeruginosa carbapenemase spectrum, alongside preserved Colistin susceptibility, underscores the importance of molecular surveillance to optimize therapy and strengthen antimicrobial stewardship in hospital settings.
Keywords: Pseudomonas aeruginosa, blaNDM carbapenemase genes, Carbapenem resistance, Colistin resistance.